Principles of marketing - Kotler, Philip; Armstrong, Gary (Gary M.) (Upper Saddle River, N.J. : Pearson Education, 2010)
'Principles of Marketing' is organized around a customer-value and customer-relationship framework. Among the learning aids in the book are: concept previews; marketing stories; concept and key term reviews; discussions on applying concepts; exercises on using technology in marketing; and situations on ethics.
'The Global edition has been edited to include enhancements making it more relevant to students outside the United States.'--P. [4] of cover.
Includes bibliographical references and index.
Keywords: Marketing